Eksistensi Pendidikan Diniyah Formal di Pondok Pesantren di Aceh - Qusyairi, Qusyairi; Zulkhairi, Teuku (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2026)
This study discusses the existence of Pendidikan Diniyah Formal (PDF) in Islamic boarding schools in Aceh as a form of Islamic education development integrated with the national formal education system. Pendidikan Diniyah Formal was established as an effort to preserve the intellectual tradition of pesantren through the study of classical Islamic texts (kitab kuning) while also providing formal legal recognition for pesantren graduates. This study aims to analyze the existence of Pendidikan Diniyah Formal in Aceh, its institutional development, and the factors that support and hinder its implementation in Islamic boarding schools. The study employed a qualitative approach using documentation studies, and interviews with parties involved in the implementation of Pendidikan Diniyah Formal in Aceh. The findings reveal that by 2023 there were 15 Pendidikan Diniyah Formal institutions spread across several regencies and cities in Aceh at the Wustha and Ulya levels. The existence of PDF demonstrates the transformation of dayah education through the integration of traditional salafiyah Islamic education with the modern formal education system without eliminating the identity of pesantren. Pendidikan Diniyah Formal also contributes to improving the quality of dayah education through a structured curriculum, diploma legality, and the strengthening of students’ religious competencies. However, the development of PDF in Aceh still faces several challenges, including limited socialization, inadequate human resources, insufficient supporting facilities, and the lack of understanding among some dayah leaders regarding the legality and system of Pendidikan Diniyah Formal. Therefore, government support, increased socialization, and stronger collaboration among pesantren are needed to expand and strengthen the existence of Pendidikan Diniyah Formal in Aceh.